Vaccination with a Human Papillomavirus (HPV)-16/18 AS04-Adjuvanted Cervical Cancer Vaccine in Korean Girls Aged 10-14 Years - Kim, Young-Jae (The Korean Academy of Medical Sciences, 2010)
The human papillomavirus (HPV)-16/18 AS04-adjuvanted cervical cancer vaccine has been demonstrated to be highly efficacious and immunogenic with a favorable safety profile. This study assessed the immunogenicity and safety of the HPV-16/18 AS04-adjuvanted vaccine in healthy Korean girls aged 10-14 yr. This multi-center, observer-blind trial randomly assigned 321 healthy girls to receive three doses (0, 1, 6-month schedule) of HPV-16/18 AS04-adjuvanted vaccine or hepatitis A vaccine. Immunogenicity against vaccine antigens was assessed one month post-Dose 3. Solicited and unsolicited adverse events (AEs) and serious AEs (SAEs) were recorded. In the according-to-protocol analysis, all initially seronegative subjects vaccinated with the HPV-16/18 AS04-adjuvanted vaccine had seroconverted at Month 7, with a peak geometric mean titer (GMT) that was 600-fold higher than the natural infection titer of 29.8 EU/mL for HPV-16 and a peak GMT that was 400-fold higher than the natural infection titer of 22.6 EU/mL for HPV-18. The vaccine was well tolerated with no increase in reactogenicity with subsequent doses and no reports of vaccine-related SAEs. In conclusion, the HPV-16/18 AS04-adjuvanted vaccine is shown to be highly immunogenic and generally well-tolerated in Korean girls aged 10-14 yr.